THE RELATIONSHIP BETWEEN SOCIAL NETWORK SITES AND SOCIAL ANXIETY AMONG UNIVERSITI PUTRA MALAYSIA UNDERGRADUATE STUDENTS. - Royal Owunna; Alice Ajobi; Angela Ahamefule; Fadero Oluwafemi Emmanuel (Paedagogia: Jurnal Pendidikan, 2022)
The study explore the relationship between social media communication and social anxiety among undergraduate students. The respondents were selected using a simple random technique. The data was collected by self-administered interview among 100 undergraduate students in Universiti Putra Malaysia. The Instruments used for data collection includes; Social Anxiety Questionnaire for Adults (SAQ-A30) and The Internet Addiction Test (IAT). Study revealed that Facebook was the most common social media patronized with 36 (36.70%) patronage, followed by Instagram with 33 (33.70%), WhatsApp 19 (19.40%) and finally Twitter with 10 (10.20%). Based on the respondents, most students use the social media for social communications and seeking information. The level of social anxiety among most undergraduate students of Human Ecology faculty in Universiti Putra Malaysia is high because approximately two third of the respondents possessed the higher score in social anxiety level.This implies that most undergraduate students of Universiti Putra Malaysia are up to date in information gathering and the use of social network has helped to facilitate social interaction among fellow students and friends thereby reducing the likelihood of students suffering social anxiety disorder.